Survivor for the surviving - My, Samedy, author (Phnom Penh : s.n., 1997)
Author's account as a physician under the Khmer Rouge Regime
Original title unknown
Translation from Khmer and French
Keywords: Physicians -- Biography -- Cambodia; Genocide -- Cambodia; Cambodia -- Politics and government -- 1975-1979